Intensified support for juvenile offenders on probation: Evidence from Germany. Issue 2 (19th April 2022) - Engel, Christoph; Goerg, Sebastian J.; Traxler, Christian
Abstract: This paper studies a probation program in Cologne, Germany. The program, which has a clear rehabilitative focus, offers intensified personal support to serious juvenile offenders over the first 6 months of their probation period. To evaluate the program's impact on recidivism, we draw on two research designs. Firstly, a small‐scale randomized trial assigns offenders to probation with regular or intensified support. Secondly, a regression discontinuity design exploits a cutoff that defines program eligibility. The results suggest that the program reduces recidivism. The effect seems persistent over at least 3 years. Our evidence further indicates that the drop in recidivism is strongest among less severe offenders.